Effects of the administration of Shinbaro 2 in a rat lumbar disk herniation model - Kim, Won Kyung; Shin, Joon-Shik; Lee, Jinho; Koh, Wonil; Ha, In-Hyuk; Park, Hyen Joo; Lee, Sang Kook; Hong, Jin Young (Frontiers in Neurology, 2023)
The current standard for the pharmacological management of lumbar disk herniation (LDH), involving non-steroidal anti-inflammatory drugs, muscle relaxants, and opioid analgesics, often carries a risk of adverse events. The search for alternative therapeutic options remains a vital objective, given the high prevalence of LDH and the critical impact on the quality of life. Shinbaro 2 is a clinically effective herbal acupuncture against inflammation and various musculoskeletal disorders. Therefore, we explored whether Shinbaro 2 exerts protective effects in an LDH rat model. The results showed that Shinbaro 2 suppressed pro-inflammatory cytokines, interleukin-1 beta, tumor necrosis factor-alpha, disk degeneration-related factors, matrix metalloproteinase-1,−3,−9, and ADAMTS-5 in LDH rats. Shinbaro 2 administration reinstated a behavioral activity to a normal level in the windmill test. The results indicated that Shinbaro 2 administration restored spinal cord morphology and functions in the LDH model. Therefore, Shinbaro 2 exerted a protective effect in LDH via actions on inflammatory responses and disk degeneration, indicating that future research is warranted to assess the action mechanisms further and validate its effects.